Ending tuberculosis: challenges and opportunities - Gilmour, Beth; Alene, Kefyalew Addis (Frontiers in Tuberculosis, 2024)
Despite impacting mankind since ancient times, tuberculosis (TB) persists as the leading cause of death from an infectious disease. TB can remain latent and further research is required to understand activation risk and the risks vs. the benefits of treating latent infection. Drug resistance poses an escalating threat to treating active disease and achieving cure. Recent advances in molecular and epidemiological techniques facilitate early diagnosis, drug susceptibility testing and an opportunity to better understand transmission dynamics. Research is ongoing to develop safe, efficacious tolerable drug regimens and the challenges of antibiotic resistance have led to a resurgent interest in therapeutic alternatives. Vaccine development is challenged by the pathogen's genetic diversity, the heterogeneity of host susceptibility and the extreme complexities that occur across the interactions between TB and its host. Across all stages of TB pathogenesis, developments in artificial intelligence, geographic information systems, digital health technologies, renewable energy solutions and nano medicine are providing opportunities to improve TB control. Resource constraints however often challenge the opportunity to access these new technologies by those most in need. The societal inequalities in accessing new technologies further compound socio-economic and health related TB determinants Addressing these complex determinants which include malnutrition, HIV infection, diabetes, substance abuse, poor environmental conditions and multi-factorial barriers to health care access, will require political will, sufficient funding, and a holistic multisectoral response.